Life Skill Education at Course Institutions at Tegal and Its Challenges in 21st Century Era - Apriani Fristianingroem , Dewi (Antroposen: Journal of Social Studies and Humaniora, 2022)
This study aims to analyze life skill education at course institution in Tegal and how life skill could defend existence of more complex life in 21st century. This research finding showed that education at course institution in Tegal had spirits to improve competences if they did want to be left by the civilization. As the competence owned by course institution in Tegal, life skill does not only cover hard and specific skills, but also spiritual skill. Those three skill principle is if human wants to success, human cannot only rely on material and non-material contents. Human needs spiritual content to be considered. It could be concluded that life skill should meet three skill contents: generic, specific, and spiritual skill (SS). Those skills are united into a bound to avoid any failures and to remain still from difficult and complex global challenges.